The Effects of Soy Protein and Cocoa With or Without Isoflavones on Glycemic Control in Type 2 Diabetes. A Double-Blind, Randomized, Placebo-Controlled Study - Konya, Judit; Sathyapalan, Thozhukat; Kilpatrick, Eric S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Objective. Soy and cocoa have been suggested to be beneficial for diabetes. The aim of this study was to identify the effects of soy protein, isoflavones and cocoa on glycemic control parameters. Research design and methods. The study was a parallel, double-blind, placebo-controlled study where patients with diet or metformin controlled type 2 diabetes were randomized to, casein soy protein with or without isoflavones (SPI, SP), and with or without cocoa (SPIC, SPC) arms for an eight week period. Glycemic control and cardiovascular risk factors were assessed prior to and after the completion of the dietary intervention. 60 participants completed the study. Results. Soy protein improved HbA1c compared to casein (p<0.05). The addition of isoflavones improved indices of insulin resistance and LDL [delta QUICKIE (SPI: -0.12 + 0.04 vs SP: 0.03 + 0.06, p=0.03); delta LDL (-0.27 + 0.41 vs 0.22 + 0.43, p=0.02); percentage change in HOMA (31.02 + 54.75 vs -14.42 + 27.07, p=0.02); percentage change in QUICKIE (-3.89 + 7.07 vs 6.11 + 10.54, p=0.01)]. However the addition of cocoa provided no benefit with or without isoflavones. Summary. Soy protein had intrinsic activity on glycemic control compared to casein. Isoflavones improved both insulin resistance and LDL, but cocoa did not have added benefit on these indices.